2006
DOI: 10.1152/ajpregu.00898.2005
|View full text |Cite
|
Sign up to set email alerts
|

High-protein nutrition during pregnancy and lactation programs blood pressure, food efficiency, and body weight of the offspring in a sex-dependent manner

Abstract: Maternal low-protein diet during pregnancy is a risk factor for cardiovascular disease of the offspring in later life. The impact of high-protein diet during pregnancy on the cardiovascular phenotype of the offspring, however, is still unknown. We examined the influence of a high-protein diet during pregnancy and lactation on the renal, hemodynamic, and metabolic phenotype of the F1 generation. Female Wistar rats were either fed a normal protein diet (20% protein: NP) or an isocaloric high-protein diet (40% pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
87
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(94 citation statements)
references
References 31 publications
6
87
0
Order By: Relevance
“…Similar results were obtained in rats fed HP diets with reduced carbohydrate content (Jean et al, 2001; -E-mail: metges@fbn-dummerstorf.de Lacroix et al, 2004). Reports on the impact of an increased dietary protein intake during gestation and lactation on maternal and foetal/offspring health and development are scarce and the results obtained are inconsistent (Daenzer et al, 2002;Zhang et al, 2005;Thone-Reineke et al, 2006). However, there seems to be a similarity with the effects of a low-protein diet that also causes decreased birth weight and altered body mass (BM) development of the offspring during lactation (Fagundes et al, 2007;Desai et al, 1996and 1997.…”
Section: Introductionsupporting
confidence: 52%
“…Similar results were obtained in rats fed HP diets with reduced carbohydrate content (Jean et al, 2001; -E-mail: metges@fbn-dummerstorf.de Lacroix et al, 2004). Reports on the impact of an increased dietary protein intake during gestation and lactation on maternal and foetal/offspring health and development are scarce and the results obtained are inconsistent (Daenzer et al, 2002;Zhang et al, 2005;Thone-Reineke et al, 2006). However, there seems to be a similarity with the effects of a low-protein diet that also causes decreased birth weight and altered body mass (BM) development of the offspring during lactation (Fagundes et al, 2007;Desai et al, 1996and 1997.…”
Section: Introductionsupporting
confidence: 52%
“…It has been shown that the induction of an altered phenotype by a maternal proteinrestricted diet during pregnancy involves changes in DNA methylation and histone modifications in specific genes, including the glucocorticoid receptor (33 % lower; P, 0·001) and PPARa (26 % lower; P, 0·05) in the liver of juvenile and adult offspring (33,34) , as well as hepatocyte nuclear factor 4a (Hnf4a) in pancreatic islets (35) . However, a high protein intake in rats during pregnancy and lactation also results in male offspring with higher blood pressure and female offspring with higher body mass and increased fat pad mass; it is possible to speculate that these effects are also mediated by epigenetic mechanisms (36) . Maurer & Reimer (37) showed that a maternal highprotein diet, but not high-prebiotic fibre diet, during pregnancy and lactation could negatively influence the expression of genes involved in glucose and lipid metabolism in the offspring rats.…”
Section: Epigenetic Mechanisms Elicited By Maternal Diet During Pregnmentioning
confidence: 99%
“…2;6 Some animal studies provide evidence in support of the suggestion that 'programming' effects may be sex-specific. [7][8][9][10] A recent meta-analysis of findings from 30 studies of the association between birthweight and total cholesterol 3 reported a sex difference, with a stronger inverse association among males than females. However, the possibility was recognised 3 that the meta-analysis was driven by results from the only two studies which found this sex difference to be significant, 11;12 especially as one study 11 was much larger than any other (n=25,843).…”
Section: Introductionmentioning
confidence: 99%